Corruption in Iraq and its reflection on financial performance - Saud, Abdulridha H.; Abdulhasan , Mohammed F. N. Al- (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to determine some of the effects caused by financial and administrative corruption on the financial performance of the Iraqi state during the period 2017-2018, and the research was based on the hypothesis that there are effects of corruption that prevent the achievement of large allocations in the current budget for the planned goals, and the analysis and comparison of the allocated and disbursed amounts have been approved for governorates and ministries, which were obtained from the Iraqi Ministry of Finance. The research has reached a number of conclusions, the most important of which are that the current anti-corruption measures all represent subsequent control and accountability of the administrative procedure or spending, and therefore the waste of money occurs and accountability is at a later time and after a period that may be relatively long, and the researchers have recommended the necessity of adopting new methods that focus on The presence of previous control of the financial or administrative event, and perhaps transparency is one of the important pillars of creating previous community control.